Organic photoelectric detector for image sensor and manufacturing method thereof - AN TAO; WU JUNYU (2018)
The invention discloses an organic photoelectric detector for an image sensor. The organic photoelectric detector comprises a glass substrate, wherein an upper surface of the glass substrate is provided with an ITO electrode layer, the upper surface of the glass substrate is sequentially coated with an anode buffer layer, a front absorption layer, a main body active layer, a cathode buffer layer and an Al electrode layer from down to up, the anode buffer layer is composed of a MoO3 layer and an NPB layer, the front absorption layer is a P3HT layer, the main body active layer is a composite layer of an electron donor material PBDT-TT-F and an electron acceptor material PC71BM, and the cathode buffer layer is composed of a BCP layer and a MoO3 layer. The absorption spectrum complementation principle is utilized, and the response scope is further expanded. The invention further discloses a manufacturing method of the organic photoelectric detector, the process is simple, and equipment requirements are low. 本发明公开